A School-Based Prevention Model in the Fight Against Addiction: Life Skills Training - CANEL, AZİZE NİLGÜN (TURKISH GREEN CRESCENT SOC, 2015)
This literature review study examines Life Skills Training, which has been widely used in the world; the development, planning, and implementation of prevention programs based on life skills and schools will be discussed. In this study, the concepts of life skills will be discussed first; information will then be given about Life Skills Training's structure and content; suggestions about its use in Turkey will be made after considering the studies that have examined the effectiveness of Life Skills Training.
Keywords: Life Skills Training; Addiction prevention; School-based programs